THE EFFECTS OF COMPENSATION, NON-PHYSICAL WORKING ENVIRONMENT, AND WORK MOTIVATION TOWARDS EMPLOYEES’ JOB SATISFACTION IN SANAN TEMPEH CHIPS INDUSTRIAL CENTER - Hanif Ananto Wibowo (Universitas muhammadiyah malang, 2017)
This study aimed to describe the compensation, non-physical working environment, motivation, and employees’ job satisfaction in Sanan Tempeh Chips Industrial Center, to figure out the simultaneous and partial effects of compensation, non-physical working environment, and motivation towards the employees’ job satisfaction, and to know which one of the independent variables having the greatest influence on the dependent one. There were 100 employees of the production unit used as respondents. The data collection techniques used were Interview, Observation, and Questionnaire. The data were analyzed by Likert Scale, Classical Assumption Test, and Multiple Linear Regression. The findings showed that the variable of compensation was categorized as “good” while variables of non-physical working environment, motivation, and job satisfaction were categorized as “fair”. Moreover, the variables of compensation, non-physical working environment, and motivation significantly affected the variable of job satisfaction. The compensation significantly and positively affected the job satisfaction. Meanwhile, the compensation, non-physical working environment, and motivation partially affected the job satisfaction. Among all the independent variables, the non-physical working environment had the greatest influence towards the employees’ job satisfaction.